Odpowiedzi

2010-03-03T18:03:31+01:00
Piszę od razu rozwiązania :P

a) = a + b + 2a - b = 3a
b) = 2x + 3y - 2z + 3z - 2x = 3y + z
c) = - 5 ab + bc - 2ab + 4 bc = - 7ab + 5bc
d) = 5 xyz - 2 xz + 4xz - 7xyz = - 2 xyz + 2 xz
e) m + n - 2m - 3n = - m - 2 n
f) = 3abc - 2abc - 5 abc = - 4abc

omiyage źle zrobiła, bo nie zmieniała znaków, jak usuwała nawiasy.. :]
2010-03-03T18:05:00+01:00
A) (a + b) + (2a - b) = 3a
b) 2x + (3y - 2z) + (3z - 2x) = 3y + 1z
c) -5ab + (bc - 2ab) + 4cb = -7ab + bc + 4cd
d) (5xyz - 2xz) + (4zx - 7zyx) = -2 xyz + 4zx
e) (m + n) - (2m + 3n) = -m + 4n
f) 3abc - (2cab + 5bac) = 3abc - 2cab + 5bac
2 3 2
2010-03-03T18:07:13+01:00
A+b+2a-b=3a
2x+3y-2z+3z-2x=z+3y
-5ab+bc-2ab+4cb=-3ab+5cb-2ab
5xyz - 2xz + 4zx - 7zyx = -2xyz - 2 xz
m +n - 2m + 3 n= m + 4 n
3abc-2cab + 5 bac= 6 abc
1 5 1